2023
DOI: 10.3389/fmicb.2023.1154765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of liquid smoke preparations on shelf life and growth of wild type mold and Aspergillus flavus in a model semi moist pet food

Abstract: Liquid smoke is a naturally derived flavor component and preservative with known antimicrobial properties. To our knowledge, there is a paucity of information on antifungal potential of liquid smoke against toxigenic fungi like Aspergillus flavus that produce mycotoxins in human and pet foods. Semi-moist pet food with high moisture content (20–30%) is susceptible to mold contamination and requires intervention. The objectives of this study were to determine the effects of liquid smoke preparations on the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…putrescentiae is also called mold mite as the presence of mold on food substrates helps proliferate this mite species as it feeds on the mold. In previous works by Deliephan et al [57][58][59], it was reported that liquid smoke can be used in pet food to enhance food safety, and the liquid smoke preparations Cloud S-C100 and Cloud S-AC15 containing medium to high phenols had a fungistatic and fungicidal effect on the growth of the storage mold Aspergillus flavus in semi-moist pet food at concentration levels of 1% to 2%. This mold-inhibiting potential of liquid smoke can be an added advantage to deter mite infestation in semi-moist foods with the inclusion of liquid smoke.…”
Section: Discussionmentioning
confidence: 99%
“…putrescentiae is also called mold mite as the presence of mold on food substrates helps proliferate this mite species as it feeds on the mold. In previous works by Deliephan et al [57][58][59], it was reported that liquid smoke can be used in pet food to enhance food safety, and the liquid smoke preparations Cloud S-C100 and Cloud S-AC15 containing medium to high phenols had a fungistatic and fungicidal effect on the growth of the storage mold Aspergillus flavus in semi-moist pet food at concentration levels of 1% to 2%. This mold-inhibiting potential of liquid smoke can be an added advantage to deter mite infestation in semi-moist foods with the inclusion of liquid smoke.…”
Section: Discussionmentioning
confidence: 99%